2009
DOI: 10.1002/chem.200802377
|View full text |Cite
|
Sign up to set email alerts
|

Selective Extraction and Transport of the [PtCl6]2−Anion through Outer‐Sphere Coordination Chemistry

Abstract: A series of tripodal receptors designed to recognise the outer coordination sphere of the hexachlorometallate anion [PtCl(6)](2-), and thus show selectivity for ion-pair formation over chloride binding, has been synthesised and characterised. The tripodal ligands contain urea, amido or sulfonamido hydrogen-bond donors, which are aligned to bind to the regions of greatest electron density along the faces and edges of the octahedral anion. The ligand structure incorporates a protonatable bridgehead nitrogen cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 50 publications
(48 reference statements)
3
44
0
Order By: Relevance
“…2b) strongly suggested that adsorption occurred by an outer-sphere, electrostatic process similar to Eq. (2) [37]. This conclusion is supported by other observations that the hexachloro complex is fairly inert to chloride loss [38].…”
Section: Template Synthesis Of Silica Np-supported Nanocatalystssupporting
confidence: 76%
“…2b) strongly suggested that adsorption occurred by an outer-sphere, electrostatic process similar to Eq. (2) [37]. This conclusion is supported by other observations that the hexachloro complex is fairly inert to chloride loss [38].…”
Section: Template Synthesis Of Silica Np-supported Nanocatalystssupporting
confidence: 76%
“…The tripodal ligands H 3 MOST, H 3 TST, and H 3 PST were synthesized following literature procedures with modifications–see supporting information for details. 2628 …”
Section: Methodsmentioning
confidence: 99%
“…3 35 Compounds 1-4 were synthesised by modifications of literature procedures (see ESI). 9 Proton NMR titration techniques were used to assess the stability of the receptor:anion complexes. Stability constants for the ligand-anion complexes were determined using the 40 EQNMR computer programme.…”
mentioning
confidence: 99%